Diagnostic capabilities of magnetic resonance imaging in assessing the state of the large and small intestines - Sementsov, O. S.; Ponomarenko, V. V. (Modern medical technology, 2021)
Purpose of the study. Purpose of the work is to show the possibilities of radiation diagnosis of the normal anatomy of the small and large intestine, as well as their pathological changes through the use of MRI (Hydro-MRI). Materials nad methods. Thirty patients were examined by the method of Hydro-MRI. All patients underwent magnetic resonance imaging on a device with a magnetic induction of 1,5 T. To carry out Hydro-MRI, we used T2-weighted sequences, such as a one-time fast spin echo signal obtained in several planes, STIR sequences in three mutually perpendicular sequences, so that edema wall edema can be estimated with additional diffusion-weighted images. Results. Twentypatientswiththemanifestations of Crohn’s disease in the form of terminal ileitis, presence of interlope fistulous passages, paraproctitis (fistulous form) were detected. Colon tumors were detected in 8 patients, recurrence of gastrointestinal stromal tumor (GIST) of the small intestine in the anastomosis zone was detected in one patient, and no pathological changes were detected in one patient. Conclusion. Hydro-MRI allows visualizing the mass of the small, large intestine and determining the degree of invasion of the intestinal wall and surrounding tissues. Enterography using magnetic resonance enterography has become the most effective methods for visualizing the small intestine in patients with Crohn’s disease and can visualize inflammation of the intramural or proximal small intestine in about 50% of patients with Crohn’s disease who have undergone endoscopically normal studies. Hydro-MRI is indicated for Crohn’s disease and for determining the degree of inflammatory activity. Recent evidence suggests that cross-section visualization may be useful in determining response to therapy, assessing bowel healing and monitoring disease progression. Also, according to researchers at the Medical Imaging Center, University College London, the quantitative motility of the small intestine is an objective biomarker of endoscopic and histopathological inflammatory activity in Crohn’s disease and is comparable to previously confirmed estimates of MRI activity enhanced by gadolinium. The final ileal mobility indicator showed a good correlation with endoscopic and histopathological activity in Crohn’s disease. The study is painless, no radiation load. Hydro-MRI is a method of choice, when it is impossible to conduct an X-ray examination of the intestine, the inability/ uninformativeness of an endoscopic examination of the small, large intestine. Along with video capsular endoscopy, it allows visualization of all departments of the small and large intestine.